1993
DOI: 10.3109/00952999309001638
|View full text |Cite
|
Sign up to set email alerts
|

Rational Recovery: Alternative to AA for Addict ion?

Abstract: Rational Recovery (RR) is a new self-help movement for substance abusers, with a cognitive orientation. It has been suggested as an alternative to Alcoholics Anonymous. This study was designed to examine the nature of RR and its impact on those who join. A national sample of 433 substance-abusing people attending 63 established RR groups was evaluated, using codable self-report questionnaires completed at RR meetings. Members were mostly men with college experience who had previously attended AA. Among recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…However, the bulk of the available evidence pertains only to 12-step mutual-help participation (e.g., AA involvement; Humphreys, 2004;Kelly, 2003). Other mutual-help organizations have been in existence for decades (e.g., Rational Recovery, SMART Recovery, Secular Organization for Sobriety, Women for Sobriety, Moderation Management); yet, only a handful of descriptive, crosssectional studies have reported information on these other groups (Connors and Derman, 1996;Galanter et al, 1993;Humphreys and Klaw, 2001;Kaskutas 1996aKaskutas , 1996bLi et al, 2000). Thus, one aim of the current study is to assess and describe rates of participation in all forms of mutualhelp groups.…”
Section: Which Mutual-help Organizations Do Patients Attend and Whichmentioning
confidence: 96%
“…However, the bulk of the available evidence pertains only to 12-step mutual-help participation (e.g., AA involvement; Humphreys, 2004;Kelly, 2003). Other mutual-help organizations have been in existence for decades (e.g., Rational Recovery, SMART Recovery, Secular Organization for Sobriety, Women for Sobriety, Moderation Management); yet, only a handful of descriptive, crosssectional studies have reported information on these other groups (Connors and Derman, 1996;Galanter et al, 1993;Humphreys and Klaw, 2001;Kaskutas 1996aKaskutas , 1996bLi et al, 2000). Thus, one aim of the current study is to assess and describe rates of participation in all forms of mutualhelp groups.…”
Section: Which Mutual-help Organizations Do Patients Attend and Whichmentioning
confidence: 96%
“…Humphreys and Moos (2001) contrasted between patients attending programs that emphasized Twelve-Step treatment and those oriented toward cognitive-behavioral approaches; the former required less subsequent inpatient hospitalization than those in the latter treatment programs. AA may also be useful as a model for approaches to promoting recovery that are not grounded on spiritual philosophy, such as a peer support program (e.g., Rational Recovery; Galanter, Egelko, & Edwards, 1993). To draw on the benefits of mutual support for abstinence, we developed a secularly grounded peer-based approach applied in ambulatory care.…”
Section: Aa and Remission From Chronic Diseasementioning
confidence: 99%
“…Several cross-sectional studies have examined mutual help alternatives, but most have focused on a single mutual help group, including WFS (Kaskutas, 1989, 1992, 1994, 1996a, 1996b, 1996c), SMART (Kelly, Deane, & Baker, 2015; O’Sullivan, Blum, Watts, & Bates, 2015), SOS (Connors & Dermen, 1996), and Rational Recovery (Galanter, Egelko, & Edwards, 1993). These studies have reliably reported positive associations between length/intensity of involvement and length of sobriety (as well as other beneficial outcomes).…”
Section: Introductionmentioning
confidence: 99%